2022
DOI: 10.3389/fpubh.2022.910055
|View full text |Cite
|
Sign up to set email alerts
|

Pivoting from systems “thinking” to systems “doing” in health systems—Documenting stakeholder perspectives from Southeast Asia

Abstract: Applications of systems thinking in the context of Health Policy and Systems Research have been scarce, particularly in Low- and Middle-Income Countries (LMICs). Given the urgent need for addressing implementation challenges, the WHO Alliance for Health Policy and Systems Research, in collaboration with partners across five global regions, recently initiated a global community of practice for applied systems thinking in policy and practice contexts within LMICs. Individual one on one calls were conducted with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…It is possible that the English-language focus of this scoping review contributed to the low number of studies identified from non-Anglophone countries, and it is recommended that future reviews are conducted to identify literature in other languages. A recent study on stakeholder perspectives of systems thinking in Southeast Asia found that some participants believed that "the nomenclature of systems thinking, and interrelated concepts were all in English and predominantly adopted a Western approach to implementation, which could have (in part) served as an impediment to wide-scale adoption" in that region [105]. Collating more examples in which systems thinking has been applied in non-Anglophone regions may assist in overcoming the perception that it is a Western construct with little application to other global contexts.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the English-language focus of this scoping review contributed to the low number of studies identified from non-Anglophone countries, and it is recommended that future reviews are conducted to identify literature in other languages. A recent study on stakeholder perspectives of systems thinking in Southeast Asia found that some participants believed that "the nomenclature of systems thinking, and interrelated concepts were all in English and predominantly adopted a Western approach to implementation, which could have (in part) served as an impediment to wide-scale adoption" in that region [105]. Collating more examples in which systems thinking has been applied in non-Anglophone regions may assist in overcoming the perception that it is a Western construct with little application to other global contexts.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of systems thinking for public health, there has been a disconnect between the practices of model developers and the needs of end users for tangible assistance [19]. On one side, modelers have invested considerable energy in thorough inventories of the factors and relationships that create a complex system.…”
Section: Introductionmentioning
confidence: 99%
“…The intention was to provide policymakers with comprehensive tools that support systems thinking approaches. Little was known about how policymakers engaged with systems thinking [19]; hence, assumptions were made and occasionally became problematic. Specifically, the laudable aim that policymakers should be provided with very comprehensive maps of causes and interrelationships implicitly assumed that they wanted such maps and would be able to use them effectively via existing software.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation